A comprehensive evaluation index system for low-carbon development of power systems in a load-intensive city - Liang, Yi; Dong, Hong; Gao, Yuqun; Hu, Liujun; Gao, Yanna; Lin, Zihan; Zeng, Fanhong; Xu, Yunxia (Frontiers in Energy Research, 2024)
There is a relative lack of research aimed at developing a comprehensive index system for low-carbon development of power systems in load-intensive cities in China. First, this paper outlined the main challenges faced in the urban power system development process and determined development goals and key indexes that combined the macro goals and requirements of constructing new power systems with the development characteristics and trends of load-intensive urban power systems. Second, a comprehensive index system and evaluation method for the low-carbon development of power systems was proposed to consider the perspectives of safety, efficiency, clean energy, low carbon, and flexibility. Finally, the effectiveness of the proposed index system and evaluation method was verified by taking the development of actual power systems in ultra-large-load-intensive cities as an example, providing support for the development decision making of actual urban power system construction and transformation.